Manajemen Sumber Daya Manusia Dalam Peningkatan Mutu Pendidikan Di DTA Jariyatul Mu’minin - Puteri, Rasdica Denara Hernowo; Nur Fadilah Ahmad; Neng Listina Ramadan; Syifa Sari Sakinah (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Education at Dayah Tarbiyatul Athfal (DTA) Jariyatul Mu'minin in Mekarmaju Village is considered the main foundation for the nation's progress. In facing the challenges of globalization, human resource management (HR) becomes crucial, especially in producing a quality generation. Effective human resource management at DTA Jariyatul Mu'minin not only includes recruitment and development, but also focuses on the welfare and motivation of educators. Efforts to improve the quality of education are not only visible from the quality of graduates, but also from how institutions meet national and service quality standards. This research analyzes using HR Planning theory to consider individual, organizational and national interests, with the aim of increasing individual potential and providing qualified employees. Research involving Real Work Lecture (KKN) students in the teaching process shows a positive contribution to developing student skills and improving the quality of education at DTA Al Jariyatul Mu'minin. Even though there has been progress, institutions realize the need to continue to improve human resource management for quality and sustainable Islamic education